The Clinical Utility of Asbestos Body Counts in Bronchoalveolar Lavage Fluid - Tsukada, Yoshikazu; Miura, Hirotaro; Shimizu, Takashi; Takayama, Shigemitsu; Takabe, Kazuhiko; Takagiwa, Jun; Aida, Shinsuke; Nakayama, Morito; Hirayama, Minoru; Akabane, Hisamasa (Nihon Kyōbu Shikkan Gakkai zasshi, 1997)
To assess the clinical utility of measuring the number of asbestos bodies (AB) present in bronchoalveolar lavage fluid (BALF), we counted the number of AB in BALF from 119 subjects using light microscopy. The results were analyzed according to occupational histories, radiological findings of asbestos-induced lung and pleural changes, and asbestos-related diseases. The 94 subjects in group 1 had a history of dust exposure, whereas group 2 subjects (n=25) had no dust exposure. Group 1 was subdivided into subjects with obvious exposure to asbestos (group 1A, n=61), and subjects with no known exposure to asbestos (group 1B, n=33). The distribution of AB counts per ml of BALF (means±SEM) differed significantly between groups 1 and 2 (38.8±17.4 vs 0.06±0.04, p<0.0001). The AB counts were significantly different between groups 1A and 1B (57.9±26.6 vs 3.4±1.2, p=0.01). Subject, exposed to dust who had radiological evidence of pleural thickening had significantly higher AB counts than subjects in whom pleural thickening was absent (66.0±31.1 vs 5.1±4.2, p=0.03). In group 1, the BALF was positive for AB in 7 of 14 patients with pulmonary fibrosis, 4 of 5 patients with lung cancer, all 6 patients with malignant mesothelioma, and all 4 patients with benign asbestos pleural effusion. We conclude that AB counts in BALF are useful for evaluating both the history of asbestos exposure in a population exposed to dust, as well as patients having asbestos-related diseases.